Sequential applied Benzalkonium Chloride and Insulin Eye Drops Reduces Ocular Central Macular Thickness and Improves vision of Diabetics and Non-Diabetics - Herman C.I. Themen; Jerry R. Toelsie; Jerrel C. Pawiroredjo; Dinesh Jiawan; Robbert Bipat (Indonesian Vitreoretinal Society, 2020)
Introduction: Macular Edema is a rather disabling condition that can be the consequence of several disorders of the eye. Most of the time it occurs in patients suffering from diabetic eye retinopathy. The exact pathophysiological mechanism of this condition is not clear, but it is probably the result of inflammatory processes or structural and mechanical disturbances of the vitreomacular tissue. Due to this obscure pathophysiological mechanism, a targeted efficient treatment is still lacking. However, accumulating evidence is suggesting that local application of insulin might reduce the structural and functional defects of this disorder. The aim of this study is to assess the effects of sequential applied benzalkonium chloride and Insulin eye drops on the visual acuity and central macular thickness of eyes suffering from macular edema. Methods: Patients refractive to or refusing treatment with anti-VEGF agents were selected. Their visual acuity and central macular thickness were measured immediately before and until six months after treatment. The treatment consisted of twice a day application of specially prepared benzalkonium chloride and Insulin eye drops. Results are expressed as mean ± SD. The procedures followed were all in line with the guides for ethics of the hospital and were not in conflict with the declaration of Helsinki. Result: After six months, the mean visual acuity increased significantly from 0.28±0.17 to 0.53±0.27 (p = 0.001) and the central macular thickness decreased from 393±122 µm to 250±72 µm (p = 0.0001). Conclusion: Sequential applied benzalkonium chloride and insulin eye drops improve visual acuity and reduce central macular thickness in eyes suffering from macular edema. Further studies to elucidate the exact mechanism of action are necessary. Apart from this, the use of these drops may prove to be a cheaper and more efficient method to treat the rather disabling condition.